DNA Methylation of BRCA1, BRCA2, and TP53 Promoters as Biomarker for the Early Diagnosis of Simian Virus 40-Related Breast Carcinoma - Sosse, Soukayna Alaoui; Tadlaoui, Kaoutar Anouar; Saif, Imane; Benhassou, Mustapha; Elkarroumi, Mohamed; Ennaji, Moulay Mustapha (Indian journal of gynecologic oncology, 2024)
Background Breast cancer (BC) is one of the major causes of death among women. Multiple risk factors are associated with the BC development, such as viral infections including simian virus 40 ( SV40 ), genetic alterations, and epigenetics due to aberrant methylation of tumor suppressor genes. Objective The objective of this work was to analyze the methylation status of the promoters of the BRCA1 , BRCA2 , and TP53 genes and their association with SV40 infection in patients with BC. Material and methods A total of 120 patients were included in this study, including 70 cases of BC and 50 cases of normal subjects. Tissue methylation was detected by methylation-specific PCR (MSP) and statistically analyzed for clinical relevance. Results The results showed that 16 of the 70 BC cases (22.85%) were positive for the SV40 , compared to none of the normal breast samples. In contrast, methylation of the BRCA1 region was detected in 36 of the 70 tumors studied (51.42%), and in 8 of the 50 normal cases (16%). Methylation of the TP53 promoter region was observed in 64.28% of BC cases and 22% of normal cases. However, all samples were BRCA2 -free. Moreover, the frequency of TP53 methylation was higher in SV40 -infected cases [ P < 0.05], but no significant correlation was observed between SV40 methylation and BRCA1 . SV40 presence did not correlate with patient survival. Conclusion Current data suggest that epigenetic alterations in BRCA1 and TP53 play an important role in the initiation and progression of BC in our study, associated with SV40 .